"Wealth Makes Many Friends": Children Expect More Giving From Resource‐Rich Than Resource‐Poor Individuals. Issue 2 (21st August 2017) - Ahl, Richard E.; Dunham, Yarrow
Abstract : Young children show social preferences for resource‐rich individuals, although few studies have explored the causes underlying such preferences. We evaluate the viability of one candidate cause: Children believe that resource wealth relates to behavior, such that they expect the resource rich to be more likely to materially benefit others (including themselves) than the resource poor. In Studies 1 and 2 (ages 4–10), American children from predominantly middle‐income families ( n  =   94) and Indian children from lower income families ( n  =   30) predicted that the resource rich would be likelier to share with others than the resource poor. In Study 3, American children ( n  =   66) made similar predictions in an incentivized decision‐making task. The possibility that children's expectations regarding giving contribute to prowealth preferences is discussed.